Marketing Strategy of Byte Dance to Operate TikTok - Fan, Yu (Transactions on Social Science, Education and Humanities Research, 2024)
Don’t know when to started, TikTok started to stand out from all short video platforms. The emergence of TikTok not only changes people’s leisure and entertainment mean and reading habits, but also changes people’s value orientation, forming a modern TikTok culture and having a profound impact on information dissemination. After the domestic germination and expansion to overseas market, TikTok has become the top stream of the short video industry. With the continuous development of network technology, TikTok has met the needs of social development and satisfied customers’ need. However, as the development of advertisement and live streaming on TikTok, the user experience which directly related to the customer loyalty and user stickness has been more or less influenced. One of the difficulties of TikTok’s future development is commercial monetization. In order to keep operation, TikTok should focus on improve user experience and increase customer stickness. The most common way to acheive commercial monetization is to consume user experience, but TikTok’s goal is to pursue a brand-new method to ahceive commercial monetization without expending customer loyalty.